2010
DOI: 10.1021/nl101156v
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Anisotropic Thermoelectric Properties and Structures of n-Type Bi2Te2.7Se0.3

Abstract: The peak dimensionless thermoelectric figure-of-merit (ZT) of Bi(2)Te(3)-based n-type single crystals is about 0.85 in the ab plane at room temperature, which has not been improved over the last 50 years due to the high thermal conductivity of 1.65 W m(-1) K(-1) even though the power factor is 47 x 10(-4) W m(-1) K(-2). In samples with random grain orientations, we found that the thermal conductivity can be decreased by making grain size smaller through ball milling and hot pressing, but the power factor decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
489
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 640 publications
(537 citation statements)
references
References 21 publications
42
489
6
Order By: Relevance
“…6(d) It was reported that re-orientation of randomly distributed grains help to achieve a ZT enhancement of n-type Bi 2 Te 3 -based thermoelectric materials. 9,11 Here, a twice-repressing process was used to get stronger (00l)-texture, in contrast to the previous oncerepressing process, and finally higher ZT along the direction perpendicular to the press direction. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6(d) It was reported that re-orientation of randomly distributed grains help to achieve a ZT enhancement of n-type Bi 2 Te 3 -based thermoelectric materials. 9,11 Here, a twice-repressing process was used to get stronger (00l)-texture, in contrast to the previous oncerepressing process, and finally higher ZT along the direction perpendicular to the press direction. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After repressing, nanosized powders of n-type bismuth telluride showed 22% ZT enhancement. 18 Here, we present a comparative study on bulk p and n-type bismuth telluride using SPS and Spark plasma texturing (SPT), a two step process using SPS and its consequences on the microstructure, texture and thermoelectric performance.…”
mentioning
confidence: 99%
“…Z. Ren and co-workers have done a very detailed study on the anisotropic TE properties of Bi 2 Te 2.7 Se 0.3 . 1 In-plane conductivity (perpendicular to press direction) is reported to be higher for both electrical and thermal test than cross-plane (parallel to press direction) by about 10%-20%. Therefore, in this work, we applied a modified factor ~0.8 to estimate the cross-plane electrical conductivity from the experimental in-plane electrical conductivity, resulting in the modification of Equation S1 to Equation S2.…”
Section: The Calculation Of Lattice Contribution In Thermal Conductivmentioning
confidence: 95%